2012
DOI: 10.1007/s11010-012-1313-z
|View full text |Cite
|
Sign up to set email alerts
|

The key role of PGC-1α in mitochondrial biogenesis and the proliferation of pulmonary artery vascular smooth muscle cells at an early stage of hypoxic exposure

Abstract: Peroxisome proliferator activated receptor gamma coactivator 1α (PGC-1α) induced by hypoxia regulates mitochondrial biogenesis and oxidative stress. However, the potential role of PGC-1α in hypoxia-promoted proliferation of pulmonary arterial vascular smooth muscle cells (PASMCs) is completely unknown. In this study, we found that hypoxia significantly induced the expression of PGC-1α in cultured PASMCs and activated mitochondrial biogenesis through upregulation of nuclear respiratory factor-1 and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…5). Rao et al reported that hypoxia could significantly enhance mitochondrial biogenesis and therefore increase the number of mitochondria [44]. Bonnet et al indicated that hypoxia sensitivity in fawn hooded rats could engender an increased number of mitochondria in PASMCs [45].…”
Section: Discussionmentioning
confidence: 99%
“…5). Rao et al reported that hypoxia could significantly enhance mitochondrial biogenesis and therefore increase the number of mitochondria [44]. Bonnet et al indicated that hypoxia sensitivity in fawn hooded rats could engender an increased number of mitochondria in PASMCs [45].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research we had observed that PGC-1˛ was evoked by inadequate oxygen in pulmonary artery smooth muscle cells (Rao et al, 2012). To further test whether hypoxia affects PGC-1˛ in PAECs, Western blot and immunochemistry analysis were performed.…”
Section: Pgc-1˛ Expression Increases Under Hypoxia In Cultured Paecsmentioning
confidence: 99%
“…Recent findings have demonstrated elevated PGC-1˛ expression in PAH patients, and proved the necessity of PGC-1˛ in pulmonary artery smooth muscle cells during hypoxia (Mata et al, 2012;Rao et al, 2012). As there are few reports evaluating PGC-1˛ in hypoxic PAECs, we first pay attention to investigate this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PGC-1α regulates oxidative phosphorylation, mitochondrial biogenesis and respiration (22,23). Numerous previous studies have suggested that ischemia and hypoxia significantly induce the expression of PGC-1α (5)(6)(7)(8)(9)(10)(11)24,25). Arany et al (12) reported that PGC-1α was able to upregulate the expression of angiogenic factors such as VEGF, and promote the formation of new blood vessels in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%